Laricitrin 3-Rutinoside from Ginkgo biloba Fruits Prevents Damage in TNF-α-Stimulated Normal Human Dermal Fibroblasts - Sullim Lee; Yea Jung Choi; Chen Huo; Akida Alishir; Ki Sung Kang; Il-Ho Park; Taesu Jang; Ki Hyun Kim (MDPI AG, 2023)
Human skin comprises the epidermis and dermis, which perform interactive functional activities with each other in order to maintain the skin's tensile strength. In particular, the dermal layer is crucial for skin protection. However, skin aging destroys collagen and elastin fibers, causing wrinkles, pigments, and sagging. Skin aging-related factors, such as tumor necrosis factor-α (TNF-α), promote the generation of intercellular reactive oxygen species (ROS). These are known to stimulate the hypersecretion of matrix metalloproteinase-1 (MMP-1), which degrades collagen and inhibits collagen synthesis. In this study, as part of our ongoing discovery of natural products, we investigated potential natural products derived from ginkgo fruit (Ginkgo biloba fruit) with protective effects against TNF-α-induced skin aging. Phytochemical investigation of the MeOH extract of G. biloba fruits, aided by liquid chromatography-mass spectrometry, led to the isolation of 14 compounds (1-14) from the n-butanol-soluble fraction. These were structurally determined to be: (E)-coniferin (1), syringin (2), 4-hydroxybenzoic acid 4-O-β-D-glucopyranoside (3), vanillic acid 4-O-β-D-glucopyranoside (4), glucosyringic acid (5), (E)-ferulic acid 4-O-β-D-glucoside (6), (E)-sinapic acid 4-O-β-D-glucopyranoside (7), ginkgotoxin-5-glucoside (8), ginkgopanoside (9), (Z)-4-coumaric acid 4-O-β-D-glucopyranoside (10), (1'R,2'S,5'R,8'S,2'Z,4'E)-dihydrophaseic acid 3'-O-β-D-glucopyranoside (11), eucomic acid (12), rutin (13), and laricitrin 3-rutinoside (L3R) (14). Biological evaluation of the isolated compounds for their effects on intracellular ROS generation showed that, of these 14 compounds, L3R (14) inhibited TNF-α-stimulated ROS generation (p < 0.001 at 100 μM). Inhibition of ROS generation by L3R led to the suppression of MMP-1 secretion and protection against collagen degradation. The inhibitory effect of L3R was mediated by the inhibition of extracellular signal regulated kinase (ERK) phosphorylation. Furthermore, L3R diminished the secretion of pro-inflammatory cytokines interleukin 6 (IL-6) and interleukin 8 (IL-8). Based on these experimental results, L3R is a potential bioactive natural product that can be used to protect against skin damage, including aging, in cosmetics and pharmaceuticals.